Effects of an advanced spring temperature increase on parr-smolt transformation in Arctic charr (Salvelinus alpinus L.) - Bottengård, Lars (Universitetet i Tromsø, 2007)
Anadromous Arctic charr (Salvelinus alpinus (L.)) was investigated to reveal whether an advanced vernal increase in freshwater temperature results in an advanced parr-smolt transformation, measured as an increase in hypoosmoregulatory ability. First generation hatchery reared anadromous Arctic charr from Talvik Research station (69˚ N. Finmark, northern Norway) was reared under a short day regime (L:D 8:16) until 7 April when continuous light was applied. One group was held on ambient temperature, whereas a second group were given elevated temperature (6˚C) from 27 March until the ambient temperature reached 6˚C in early June. At regular intervals fish were sampled from freshwater to obtain samples for measuring gill Na+K+ATPase activity, plasma osmolality, plasma chloride concentrations and morphological data. In addition 24h seawater tests were performed at the same dates as freshwater samplings, and blood samples for plasma osmolality and plasma chloride concentrations analysis were obtained in order to investigate the ability to hypoosmoregulate in full strength seawater. The experimental fish reached full smolt status at the time of seaward migration of hatchery reared Arctic charr released into the Hals watercourse (69˚N) from Talvik Research Station. Full hypoosmoregulatory ability coincided with high Na+K+ATPase activity. No advance in hypoosmoregulatory ability was seen in the fish held on advanced elevated temperature, indicating that the development of hypoosmoregulatory ability in Arctic charr is mainly initiated by changes in photoperiod. The results indicate that a seawater temperature increase in early spring due to global warming may lead to a mismatch between optimal feeding conditions and seawater migration of Arctic charr. In the prospects of an air temperature increase in Norway of 2,5 to 4˚ C during the next decade, more research is needed for elucidating if, and how much a future global warming may affect the northernmost distributed freshwater fish. Key words: Arctic charr; Temperature; ...